USING THE THINK-PAIR-SHARE STRATEGY TO INCREASE STUDENTS’ ACTIVE INVOLVEMENT AND TO IMPROVE THEIR SPEAKING ABILITY - Muhammad Lukman Syafii (IJEE (Indonesian Journal of English Education), 2018)
ABSTRACTThis study was designed to increase students’ active involvement and to improve their speaking ability using Think-Pair-Share Strategy at Muhammadiyah University of Ponorogo. The study was collaborative action research. This study was conducted in one cycle consisting of five meetings using the following procedures: planning, implementing, observing, and reflecting. The data of the study were collected through the observation checklists, field notes, and questionnaire. The subjects were 26-second semester students of Class A. The increase could be seen from the number of students who were categorized as actively involved from only 7 students (29%) in the preliminary study to 20 students (78%) of 26 at the end of the study. The improvement of students’ speaking ability could be seen from the increasing number of students whose average score was 3, from 7 students (29%) of 24 students in the preliminary test to 17 students (65%) of 26 students in the final test. Therefore, this strategy is appropriate for the students to increase their active involvement and improve the speaking ability.ABSTRAKPenelitian ini dirancang untuk meningkatkan keaktifan dan kemampuan berbicara mahasiswa dengan menggunakan Berfikir-Berpasangan-Berbagi di Universitas Muhammadiyah Ponorogo. Penelitian ini merupakan penelitian tindakan kelas yang bersifat kolaboratif. Penelitian ini dilakukan dalam satu siklus yang terdiri dari lima pertemuan dengan menggunakan prosedur sebagai berikut: perencanaan, pelaksanaan, pengamatan dan penghayatan. Pengumpulan data dilakukan dengan menggunakan lembar observasi, catatan lapangan, dan kuesioner. Subjek penelitian ini adalah 26 mahasiswa semester 2 kelas A. Peningkatan keterlibatan aktif mahasiswa dapat dilihat dari meningkatnya jumlah mahasiswa yang termasuk dalam kategori aktif yang pada saat penelitian awal hanya 7 mahasiswa (29%) menjadi 20 mahasiswa (78%) dari 26 mahasiswa yang masuk pada saat hari observasi pertemuan terakhir. Peningkatan kemampuan berbicara mahasiswa dapat dilihat dari meningkatnya jumlah mahasiswa yang memiliki nilai rata-rata 3, dari 7 orang menjadi 17 orang. Maka dari itu, strategi ini sesuai bagi mahasiswa untuk meningkatkan keterlibatan aktif dan memperbaiki kemampuan berbicara bahasa inggris mereka. How to Cite: Syafii., M. L. (2018). Using the Think-Pair-Share Strategy to Increase Students’ Active Involvement and to Improve Their Speaking Ability. IJEE (Indonesian Journal of English Education), 5(1), 61-80. doi:10.15408/ijee.v5i1.7679